Family Capitals, Livelihood Strategies, and Family Well-Being of Plantation Worker - Nurul Salimah; Istiqlaliyah Muflikhati (Journal of Family Sciences, 2016)
This study aimed to analyze the influence of family characteristic, family capitals, and livelihood strategy toward family well-being. The sample of this study was family with wife who worked as a tea picker in Purwabakti, Pamijahan, Bogor. There were 100 families chosen randomly in this research. Family well-being was observed based on indicators defined by National Population and Family Planning Board (NPFPB) and Statistics Indonesia (SI). The analyses used in this research were descriptive analyses, independent sample T-test, and logistic regression. The result showed husband age and family size negatively affected the family well-being. Physical capital and financial capitals positively affected the family well-being. Meanwhile, livelihood strategy did not significantly affect the family well-being.Keywords: family capitals, family well-being, livelihood strategies Penelitian ini bertujuan untuk menganalisis pengaruh karakteristik keluarga, kepemilikan modal keluarga, dan strategi nafkah terhadap kesejahteraan keluarga. Contoh dalam penelitian ini adalah keluarga dengan istri yang bekerja sebagai buruh pemetik teh di Desa Purwabakti, Kecamatan Pamijahan, Kabupaten Bogor. Contoh dalam penelitian ini sebanyak 100 orang yang dipilih secara acak. Kesejahteraan keluarga diukur dengan menggunakan indikator BKKBN dan BPS. Analisis yang digunakan merupakan analisis deskriptif, uji beda independent sample T-test dan uji regresi logistik. Hasil penelitian menunjukkan umur suami dan besar keluarga berpengaruh negatif signifikan terhadap kesejahteraan keluarga. Modal fisik dan modal finansial berpengaruh positif signifikan terhadap kesejahteraan keluarga. Sementara itu, strategi nafkah tidak berpengaruh signifikan terhadap kesejahteraan keluarga.Kata kunci : kesejahteraan keluarga, modal keluarga, strategi nafkah